given y = (p+q+r) /4

multiply both sides by 4, we get

4y = (p+q+r)/4 * 4 = (p+q+r)

that is 4y = p+q+r

now to get q we have to eleminate p,q from the right side of the equation,

so take -p-r on both the sides of the equation,

...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

given y = (p+q+r) /4

multiply both sides by 4, we get

4y = (p+q+r)/4 * 4 = (p+q+r)

that is 4y = p+q+r

now to get q we have to eleminate p,q from the right side of the equation,

so take -p-r on both the sides of the equation,

4y-p-r = p+q+r-p-r = q

thus the solution for q is q = 4y-p-r